Numerical CFD Investigation of Shortboard Surfing: Fin Design vs. Cutback Turn Performance - David Shormann; Luca Oggiano; Marc in het Panhuis (Proceedings, 2020)
The surfing performance of two shortboard fin types with surface features were compared to a standard (control) fin with a smooth surface using dynamic computational fluid dynamics (CFD) simulations. The fins with surface features included designs with a partially grooved and serrated surface (CR), and humpback whale-inspired fins with tubercles and other features (RW). Surfboard roll, pitch and yaw during cutback maneuvers were simulated based on field data from surfers of intermediate, expert and professional (WCT) skill level surfing on ocean waves. Sustained resultant forces relative to the rider direction were significantly different between fin types, and lowest for RW at WCT-level rotations. CFD results also revealed RW’s ability to dampen effects of turbulent flow. RW fins were always the last to stall during a turn, and always exhibited the most gradual stall. CR fins had significantly lower pre-turn drag, and the highest mean resultant forces during the turn. Overall, CR fins appear best for forward acceleration and hold on the wave, while RW fins appear best for maneuverability and stability.